(ISC)2 CCSP Certified Cloud Security Professional official practice tests - Chapple, Mike, 1975-; Seidl, David, CISSP (Sybex, a Wiley Brand, 2022)
The only official CCSP practice test product endorsed by (ISC)2 With over 850 practice questions all new for the 2022-2025 exam objectives, (ISC)2 CCSP Certified Cloud Security Professional Official Practice Tests, 3 rd Edition gives you the opportunity to test your level of understanding and gauge your readiness for the Certified Cloud Security Professional (CCSP) exam long before the big day. These questions cover 100% of the CCSP exam domains and include answers with full explanations to help you understand the reasoning and approach for each. Logical organization by domain allows you to practice only the areas you need to bring you up to par, without wasting precious time on topics you've already mastered. As the only official practice test product for the CCSP exam endorsed by (ISC)2, this essential resource is your best bet for gaining a thorough understanding of the topic. It also illustrates the relative importance of each domain, helping you plan your remaining study time so you can go into the exam fully confident in your knowledge. When you're ready, two practice exams allow you to simulate the exam day experience and apply your own test-taking strategies with domains given in proportion to the real thing. The online learning environment and practice exams are the perfect way to prepare and make your progress easy to track. For this new Third Edition, cloud security experts Mike Chapple and David Seidl have delivered an all-new question set for the new CCSP 2022-2025 objectives. These authors are well known for their best-selling (ISC)2 CISSP Certified Information Systems Security Professional Official Practice Tests and now they've joined forces again to deliver the same high caliber practice questions for the CCSP exam.